2017
DOI: 10.1136/bmjopen-2017-017459
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the uptake of seasonal influenza vaccination in older and younger adults: a large, population-based survey in Beijing, China

Abstract: ObjectivesThe present study aimed to estimate the influenza vaccination coverage rate in Beijing, China, and identify its determinants in older and younger adults.MethodsA survey was conducted among Chinese adults using a self-administered, anonymous questionnaire in May–June 2015. The main outcome was seasonal influenza vaccination uptake. Multivariate logistic regression models were performed to identify factors associated with uptake.ResultsA total of 7106 participants completed the questionnaire. The overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 23 publications
6
49
4
Order By: Relevance
“…As described in other studies, 13,14 having received a recommendation from a healthcare professional is a strong determinant of influenza vaccination. We also found that having consulted a conventional healthcare professional over the last 12 months, such as a family doctor or a nurse was linked to influenza vaccination.…”
Section: Discussionsupporting
confidence: 58%
“…As described in other studies, 13,14 having received a recommendation from a healthcare professional is a strong determinant of influenza vaccination. We also found that having consulted a conventional healthcare professional over the last 12 months, such as a family doctor or a nurse was linked to influenza vaccination.…”
Section: Discussionsupporting
confidence: 58%
“…The participants were classified into ten subgroups according to residence (urban or suburban) and different age groups (18-29, 30-39, 40-49, 50-59 and !60 years). The formula n = l a 2  p  (1 À p)/d 2  deff was used to estimate the sample size per subgroup, based on an a error of 5%, the rate of residents' willingness to accept a future H7N9 vaccine in the general population of Beijing (p) = 50%, maximum permissible error (d) = 0.1p, and the design effect of complex sampling (deff) = 1.5 [18,19]. We estimated a sample size of 576 participants per subgroup.…”
Section: Participants and Survey Designmentioning
confidence: 99%
“…In this study, participants were recruited by a multistage stratified sampling approach [18][19][20]. Initially, three urban districts and three suburban districts were randomly selected to be sampled.…”
Section: Participants and Survey Designmentioning
confidence: 99%
“…3,4 It is well recognised that vaccine uptake may be greatly influenced by multiple factors such as, for example, lack of recommendation by general practitioners, concerns about vaccination effectiveness and safety, lack of knowledge and information, low perception of risk, difficult access to preventive activities, and socio-economic predictors. [5][6][7][8][9][10] Among the userrelated determinants affecting decisions about whether to vaccinate, parents' vaccine hesitancy represents a recent and growing concern in developed and developing countries. 11 It is well known that vaccine hesitancy refers to all kind of concerns that parents express by refusing some vaccines, delaying vaccines or accepting others, but they are unsure of doing so, despite availability of services and it is complex and context specific, varying across time, place, and vaccines.…”
Section: Introductionmentioning
confidence: 99%